Study of Ethnomatematics Sendratari Ramayana at the Ramayana Ballet in Prambanan Temple - Kinanti, Theresia Restu; Nugraha, Adhi Surya; Rudhito, Marcellinus Andy (Universitas Sarjanawiyata Tamansiswa, 2024)
The ethnomathematics learning approach is used to preserve culture in schools. In addition, it also makes it easier for students to understand abstract mathematical concepts. The culture studied was the Ramayana ballet in the Prambanan temple area. According to Bishop, this research aims to discover fundamental aspects of mathematics. The author used a qualitative approach and a literature study to collect data. In comparison, the data collection technique used in this research is library data collection obtained from literature studies that contain related sources and references. The data analysis techniques used in this research are data collection, reduction, and conclusion. The research results are 1) counting, number of accessories, and angles formed. 2) location and floor pattern. 3) measurement, duration, stage area. 4) designing, floor pattern properties, jarik motifs. 5) playing, the way dancers do not collide, and the provisions of the storyline. 6) explaining the Ramayana storyline and costume meaning.